Cobalt-nickel bimetal carbon sphere catalysts for efficient hydrolysis of sodium borohydride: The role of synergy and confine effect. (29th January 2023) - Sun, Lei; Gao, Xiaofeng; Ning, Xin; Qiu, Zhongmin; Xing, Liwei; Yang, Hua; Li, Dacheng; Dou, Jianmin; Meng, Yuanyuan
Abstract: Sodium borohydride exhibits great potential in the field of chemical hydrogen storage. A competent catalyst would accelerate its practical application for hydrogen utilization by enhance the efficiency of hydrogen generation from hydrolysis of sodium borohydride. Herein, a kind of highly efficient and durable synergistic Co–Ni bimetal inlaid carbon sphere catalyst (Co-NiΦC) was prepared by a co-pyrolysis method, of which the configuration of metal inlaid carbon sphere could effectively expose and anchor the active component by contrast with the capsule catalyst (Co–Ni@C) and supported catalyst (Co–Ni/C). Further, diverse cobalt-nickel contents of the Co-NiΦC catalysts were optimized to achieve the best hydrolysis performance of sodium borohydride. The structure-performance relationship of inlaid catalyst and the bimetallic synergistic mechanism were investigated by multiple characterization measurements and the density functional theory (DFT). As demonstrated, the inlaid Co-NiΦC-2 catalyst (Co/Ni molar ratio of 8/2) shows a promising catalytic activity of hydrogen generation rate up to 6364 mLH 2 ·min −1 ·gmetal −1, a relative low reaction activation energy of 30.3 kJ/mol as well as robust durability where it still remains about 83.4% of its initial reaction rate after the fifth cycle. The outstanding performance of the optimized catalyst may ascribe to the high dispersion, remarkable Co–Ni synergy and high stabilization of the Co–Ni nanoparticles under the confinement effect of the inlaid metal-carbon sphere configuration. This work provides an alternative avenue for the application of efficient carbon-supported bimetal catalysts in the future. Graphical abstract: Image 1 Highlights: The Co–Ni bimetal inlaid carbon sphere catalysts with highly dispersed ultra-small nanoparticles have been synthesized. The inlaid configuration has advantages in both limiting metal leaching and exposing active sites. The Co–Ni synergistic effect is beneficial to optimize the structure and electronic effect of the catalyst.